2015
DOI: 10.1002/9780471729259.mc15c06s37
|View full text |Cite
|
Sign up to set email alerts
|

Rotaviruses: Extraction and Isolation of RNA, Reassortant Strains, and NSP4 Protein

Abstract: Rotavirus (RV) contains 11 double‐stranded RNA segments that encode for twelve structural and nonstructural proteins. The separation and isolation of viral RNA is a necessary precursor for many experimental techniques and can be useful for rapid RV RNA typing and sequencing of different rotavirus strains. The segmented genome enables RV to recombine easily. These recombinant viruses are essential for many purposes, including generation of potential vaccine strains. Rotavirus gene 10 expresses the viral enterot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The characteristics of the infant's own nervous system may be one of the reasons for CwG convulsion [7,11]. Some studies have suggested that Rotavirus can disrupt calcium homeostasis by releasing the viral enterotoxin nsp4 or directly invading the central nervous system to cause CwG [18][19][20]. A study by Kim et al showed that the Rotavirus vaccine could greatly reduce the incidence of Rotavirus-induced CwG [21].…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of the infant's own nervous system may be one of the reasons for CwG convulsion [7,11]. Some studies have suggested that Rotavirus can disrupt calcium homeostasis by releasing the viral enterotoxin nsp4 or directly invading the central nervous system to cause CwG [18][19][20]. A study by Kim et al showed that the Rotavirus vaccine could greatly reduce the incidence of Rotavirus-induced CwG [21].…”
Section: Discussionmentioning
confidence: 99%
“…coli S17 donor cells by electroporation and transferred to S . maltophilia recipients via conjugation following the protocol described by Welker et al [72]. Tetracycline-resistant colonies were first selected.…”
Section: Methodsmentioning
confidence: 99%
“…NSP4 is a glycosylated protein that is important for viral replication, morphogenesis, and pathogenesis. 44 During AGE, NSP4 is responsible for intestinal secretion by altering calcium Table 1 e Factors associated with seizure development in subjects with acute gastroenteritis.…”
Section: The Epidemiology and Pathogenesis Of Cwgmentioning
confidence: 99%